(untitled) (Informatica, 2024)
In the present paper, we conduct an in-depth study on multi-styled digital music and design an artificial intelligence-based multi-styled digital theme automation-assisted composition system. In the process of system development, B/S software design architecture is selected, J2EE ecosystem-related technology is used, and the system framework is built following the principle of sub-module development. A web hosting platform is provided for the whole Internet publishing system to realise the online and real-time functions. In addition, to improve the robustness, scalability, security, and ultimately, the system’s quality of service, the functional design analysis, software architecture system, development technology, and optimisation strategy are carefully studied and discussed. After learning and analysing the file format of MIDI digital music, we chose the feature extraction method for each instrument to preserve the instrument’s characteristics. We used its parameter model for each device during the composition to ensure the instrument’s characteristics. After optimisation of the model, composition experiments were conducted, and the compositional effect was measured; the average ratio of adjacent notes with intervals within one octave was 83.57% for the composed pieces. The composition system eliminates using only a single algorithmic composition technique method in the system platform. Instead, it adopts the direction of a hybrid system that integrates multiple processes, an inevitable trend. The composition system provides flexible human-computer interaction at all music composition levels to improve the system’s usefulness and effectiveness.